Digital branding and entrepreneurship skills for millennials in Pabean Udik Village, Indramayu - Ridwan Ridwan; Ana Kuswanti; Munadhil Abdul Muqsith; Anter Venus (Community Empowerment, 2022)
Training in entrepreneurship, social media usage, and information technology is required to boost youth creativity and innovation in the digital age. The aim of this community service is to raise awareness of the importance of increasing product value and developing digital marketing strategies for products. The method is socialization, training in the production of innovative products, and digital marketing skills. The results of the program can be seen in the raise in youth entrepreneurship, the value of products, and digital marketing. The participants can use processed milkfish and seaweed to create creative products that will raise its value. Additionally, youth in Pabean Udik Village have use of online marketing tools to promote their creative products.